Determination of Surface Topography and Composition of Cr-Free Pretreatment Layers on Hot Dip Galvanized Steel - Saarimaa, Ville; Markkula, Antti; Juhanoja, Jyrki; Skrifvars, Bengt-Johan (Journal of Coating Science and Technology, 2014)
Topography and composition of Cr-free, titanium-based pretreatment layers on hot dip galvanized steel were studied with scanning electron microscopy, atomic force microscopy, time of flight secondary ion mass spectrometry and Auger electron spectroscopy. A layer within the target coating weight range (4-10 mg Ti/m2) for industrial coil coating processes contained a micro-structure with hillocks and valleys, showing significant topographical variations. A local maximum film thickness of about 50 nm was detected for a sample containing 5.0 mg Ti/m2. The hillocks were composed of metal complexes and phosphates, formed as a result of rapid zinc dissolution and metal hydroxide/phosphate precipitation reactions. During the layer formation also the polymer component of the pretreatment chemical becomes embedded within the structure. The structure composed of hillocks and valleys may be highly beneficial for paint adhesion, increasing the surface contact area for primary and secondary chemical bonding